Class Conflict in the Era of Consumerism: Proletarian Resistance to the Bourgeois Market Logic - Sudirman, Sudirman; Amir, Andi Mascunra; Saleh, Mohammad (Socious Journal, 2026)
In contemporary capitalism, consumerism operates not only as a lifestyle pattern but also as a subtle mechanism of class domination that reshapes how exploitation and resistance are experienced. This study aims to analyze how bourgeois market logic obscures class conflict through consumption, datafication, and media culture, while proletarian resistance emerges in dispersed and hybrid forms across digital, cultural, and consumer spaces. A qualitative approach using a Systematic Literature Review (SLR) was employed, examining peer-reviewed journal articles published between 2021 and 2025 from multidisciplinary sources in political economy, sociology, and cultural studies. The data were analyzed thematically to identify patterns linking consumer culture, transformed exploitation, and new resistance practices. The findings reveal that consumerism normalizes inequality by commodifying identity and attention, while digital platforms intensify algorithmic control over labor and consumption. At the same time, resistance appears through anti-consumption movements, digital collectivism, financial activism, and the creation of alternative communicative spaces. The discussion shows that class conflict persists but is relocated from traditional workplaces to market, media, and digital arenas. In conclusion, understanding contemporary class struggle requires recognizing how everyday consumption becomes a site of domination and how proletarian resistance adapts within and against the structures of bourgeois market logic.